Composite bipolar plate for flow battery as well as preparation method and application of composite bipolar plate
By doping carboxylated carbon nanotubes and blending conductive fillers and fiber reinforced materials in the composite bipolar plate for liquid flow batteries, and adopting high-speed stirring and molding processes, the problems of poor conductivity and complex preparation processes in the prior art are solved, and a high-performance and efficient preparation composite bipolar plate is achieved.
Patent Information
- Application Number
- CN202510343659.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-22
- Publication Date
- 2025-04-22
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When the existing composite bipolar plates for flow batteries improve mechanical stability, the conductivity is poor, the component uniformity is not ideal, and the preparation process is complicated, requiring multiple heating, and the energy consumption is high.
Polymer-based nanocomposites are prepared by doping carboxylated carbon nanotubes into fluoropolymers and blending them with conductive fillers and fiber reinforced materials. High-speed stirring and molding processes are used to simplify the preparation process and improve component uniformity and conductivity.
It has achieved improvements in the mechanical and conductive properties of composite bipolar plates, improved component uniformity, simplified preparation process, energy saving, and is suitable for large-scale production.
Smart Images

Figure CN119858268A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of liquid flow batteries, and in particular relates to a composite bipolar plate for a liquid flow battery and a preparation method and application thereof. Background Art
[0002] The growing energy supply from intermittent renewable energy sources requires the rapid introduction of efficient energy storage. Flow batteries are a promising technology because they can independently scale power and storage capacity according to specific requirements. In addition, flow batteries are characterized by fast response time and long cycle life of the electrolyte.
[0003] In a flow battery stack, bipolar plates are "non-active" components that conduct current from one cell to another. They physically separate adjacent cells from each other while maintaining contact with the acidic half-cell electrolyte on each side. Good bipolar plates need to have high chemical and mechanical stability, high conductivity, and impermeability to prevent leakage. Metal bipolar plates are not generally used in flow batteries because they are susceptible to corrosion in acidic environments and require a protective layer. Graphite-based bipolar plates are widely used due to their good conductivity and good chemical stability. Bipolar plates in flow batteries are usually composed of carbon material / polymer composites because they are lower cost than graphite and have higher mechanical stability. In this composite material, the polymer provides mechanical stability, while the carbon material, such as graphite, carbon black, carbon fiber or carbon nanotubes, provides conductivity.
[0004] However, in order to ensure that the bipolar plate is not easy to break and break during use, the content of polymer is often increased, but the conductivity of the bipolar plate is poor. At the same time, the differences in particle size, density and surface morphology between polymer and carbon material make the existing carbon material / polymer composite bipolar plate have the problem of unsatisfactory component uniformity. The Chinese patent document with publication number CN117207561A discloses a bipolar plate for all-vanadium liquid flow battery and its preparation method. In the mixing stage, a multi-stage heating method is adopted to enhance the interaction between components and improve the distribution uniformity of each component in the powder. At the same time, two graphite papers are pasted on the surface of the molded plate to improve the conductivity of the bipolar plate. This method improves the uniformity, conductivity and mechanical strength of the molded plate. However, this method involves the steps of multi-stage mixing and heating, the mixing process is complicated, and graphite paper is attached to the surface of the bipolar plate to improve the conductivity of the composite bipolar plate. The preparation process is relatively complicated, and the addition of graphite paper will cause the composite bipolar plate to be delaminated. Summary of the invention
[0005] The purpose of the present invention is to provide a composite bipolar plate for a liquid flow battery, and a preparation method and application thereof. By preparing a polymer-based nanocomposite material, the problem of poor compatibility between polymers and conductive fillers in the prior art can be solved, and the components of the composite bipolar plate can be evenly distributed. While maintaining good mechanical strength, the conductivity of the bipolar plate can be effectively improved. The preparation process is simple, does not require multi-step heating, can save energy, and is easy to mass produce.
[0006] In order to achieve the purpose, the present invention provides a method for preparing a composite bipolar plate for a flow battery, characterized in that it comprises the following steps: (1) treating the carbon nanotubes with an oxidation treatment using a mixed acid of concentrated nitric acid and concentrated sulfuric acid to obtain carboxylated carbon nanotubes; (2) adding the carboxylated carbon nanotubes obtained in step (1) to a mixed solution of N,N-dimethylformamide and tetrahydrofuran, ultrasonicating until completely dispersed, then adding a fluorine-containing polymer, stirring, and drying to obtain a polymer-based nanocomposite material; (3) The polymer-based nanocomposite material, the conductive filler and the fiber-reinforced material obtained in step (2) are mixed, ground for 5 to 10 minutes, and then stirred at high speed and compression molded to obtain a composite bipolar plate for a liquid flow battery.
[0007] Preferably, in step (1), the mass fraction of concentrated nitric acid is 65%-68%, the mass fraction of concentrated sulfuric acid is 95%-98%, the volume ratio of concentrated nitric acid to concentrated sulfuric acid is 1-1.5:1, and the mass volume ratio of carbon nanotubes to concentrated nitric acid-concentrated sulfuric acid mixed acid is 400-500 mg:30 mL.
[0008] Preferably, in step (2), the volume ratio of N,N-dimethylformamide to tetrahydrofuran is 1-1.5:1; the mass volume ratio of carboxylated carbon nanotubes to N,N-dimethylformamide solution is 0.28 g:50-72 mL; the fluorine-containing polymer is polyvinylidene fluoride or polyvinylidene fluoride-hexafluoropropylene copolymer; the mass ratio of the fluorine-containing polymer to the carboxylated carbon nanotubes is 29-31.5:1, the stirring time is 8-12 h, and the drying time is 10-12 h.
[0009] Preferably, in step (3), the conductive filler comprises one or both of flake graphite and expanded graphite and Ketjen black; the fiber reinforcement material is carbon nanofiber or carbon fiber; the mass ratio of the polymer-based nanocomposite material, the conductive filler, and the fiber reinforcement material is 6-6.5:3-3.7:0.3-1; and the high-speed stirring speed is 22000-24000 rpm / min for 15-30 s.
[0010] Preferably, in step (3), the compression molding temperature is 190-200° C., the pressure is 5-15 MPa, and the time is 5-15 min.
[0011] The present invention also provides a composite bipolar plate for a liquid flow battery prepared by the above preparation method.
[0012] The present invention also provides the composite bipolar plate for liquid flow battery applied to the liquid flow battery.
[0013] The beneficial effects of the present invention are: (1) The preparation method of the composite bipolar plate for liquid flow battery provided by the present invention is to prepare a polymer-based nanocomposite material by doping carboxylated carbon nanotubes in a fluorine-containing polymer. The strong interaction between the carboxyl groups in the carbon nanotubes with surface carboxyl groups and the CF2 in polyvinylidene fluoride (PVDF) and polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-hfp) is conducive to better compounding of the two powders. After high-temperature heating, the polymer can be uniformly melted and filled in the bipolar plate, thereby obtaining a composite bipolar plate with uniform material distribution. The preparation process of this method is simple, does not require multiple heating, can save energy, and is easy to carry out continuous industrial production.
[0014] (2) The method for preparing the composite bipolar plate for a flow battery provided by the present invention adopts high-speed stirring of 20,000-24,000 rpm / min, which weakens the size barrier between the components in the powder, strengthens the interaction between the polymer and the conductive carbon material, and has high dispersion efficiency and good dispersion effect. The volume of the Ketjen black after high-speed stirring is loose and expanded, and the surface of the conductive filler is not completely coated by the polymer, but exposed on the surface, so that the bipolar plate exhibits excellent and uniform conductive properties.
[0015] (3) The application of the composite bipolar plate for liquid flow batteries provided by the present invention is tested by a conductivity tester, and the conductivity of the bipolar plate reaches 108-140S / cm. The tensile strength of the bipolar plate can reach 45.26-53.52MPa and the bending strength can reach 20.05-26.33MPa when tested by a universal testing machine. Compared with the composite bipolar plate for liquid flow batteries in the prior art, the performance is better. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 In the figure, (a) is a sample picture of the composite bipolar plate for a liquid flow battery prepared in Example 5; (b) is a sample picture of the composite bipolar plate for a liquid flow battery prepared in Comparative Example 1. DETAILED DESCRIPTION Example 1
[0017] (1) 15 mL of 68% concentrated nitric acid and 15 mL of 98% concentrated sulfuric acid were sequentially added dropwise to 500 mg of carbon nanotubes. The suspension was uniformly dispersed by ultrasonication for 2 h. The mixture was centrifuged and then washed with deionized water until the pH value of the solution reached neutral. After drying, carboxylated carbon nanotubes were obtained. (2) 0.28 g of carboxylated carbon nanotubes was added to a mixed solution of 60 mL of N,N-dimethylformamide (DMF) and 40 mL of tetrahydrofuran (THF), and ultrasonicated until completely dispersed. Then, 8.12 g of PVDF was added, stirred for 8 h, and dried for 10 h to obtain a polymer-based nanocomposite material.
[0018] (3) Weigh 8.4 g of polymer-based nanocomposite, 1.4 g of Ketjen black, 3.36 g of flake graphite, and 0.84 g of carbon nanofiber; (4) Pour the weighed material into a mortar grinder and grind for 5 minutes; (5) Pour the ground material into a high-speed mixer and mix for 15 seconds, where the stirring rate of the high-speed mixer is 24000 rpm / min; (6) After the mold is coated with a release agent, the mixed material is transferred to the mold, and the mold containing the mixed material is transferred to a flat vulcanizer for compression molding. The compression molding temperature is 190° C., the compression molding pressure is 15 MPa, and the compression molding time is 10 min. The pressure is released and the mold is demolded to obtain a composite bipolar plate for a liquid flow battery with a thickness of 0.7 mm. The mass fraction of the polymer-based nanocomposite material is 60%, the mass fraction of the conductive filler is 34%, and the mass fraction of the fiber reinforcement material is 6%. Example 2
[0019] (1) 18 mL of 65% concentrated nitric acid and 12 mL of 96% concentrated sulfuric acid were sequentially added dropwise to 450 mg of carbon nanotubes. The suspension was uniformly dispersed by ultrasonication for 2 h. The mixture was centrifuged and then washed with deionized water until the pH value of the solution reached neutral. After drying, carboxylated carbon nanotubes were obtained. (2) 0.28 g of carboxylated carbon nanotubes was added to a mixed solution of 50 mL of DMF and 50 mL of THF, and ultrasonicated until completely dispersed. Then, 8.12 g of PVDF was added, stirred for 8 h, and dried for 12 h to obtain the PVDF-based nanocomposite material.
[0020] (3) Weigh 8.4 g of PVDF-based nanocomposite, 0.56 g of flake graphite, 1.4 g of Ketjen black, 2.8 g of expanded graphite, and 0.84 g of carbon nanofiber; (4) Pour the weighed material into a mortar grinder and grind for 10 minutes; (5) Pour the ground material into a high-speed mixer and mix for 15 seconds, where the stirring rate of the high-speed mixer is 22000 rpm / min; (6) After the mold is coated with a release agent, the mixed material is transferred to the mold, and the mold containing the mixed material is transferred to a flat vulcanizer for compression molding. The compression molding temperature is 200° C., the compression molding pressure is 15 MPa, and the compression molding time is 15 min. The pressure is released and the mold is demolded to obtain a composite bipolar plate for a liquid flow battery with a thickness of 0.6 mm. The mass fraction of the polymer-based nanocomposite material is 60%, the mass fraction of the conductive filler is 34%, and the mass fraction of the fiber reinforcement material is 6%. Example 3
[0021] (1) 15 mL of 66% concentrated nitric acid and 15 mL of 95% concentrated sulfuric acid were sequentially added dropwise to 400 mg of carbon nanotubes, the suspension was uniformly dispersed by ultrasonication for 2 h, the mixture was centrifuged, and then washed with deionized water until the pH value of the solution reached neutral, and then dried to obtain carboxylated carbon nanotubes; (2) 0.28 g of carboxylated carbon nanotubes was added to a mixed solution of 72 mL of DMF and 48 mL of THF, and ultrasonicated until completely dispersed. Then, 8.82 g of PVDF-hfp was added, stirred for 12 h, and dried for 12 h to obtain the PVDF-hfp-based nanocomposite material.
[0022] (3) Weigh 9.1 g PVDF-HFP-based nanocomposite, 0.84 g Ketjen black, 3.5 g flake graphite, and 0.56 g carbon nanofiber; (4) Pour the weighed material into a mortar grinder and grind for 10 minutes; (5) Pour the ground material into a high-speed mixer and mix for 20 seconds, where the stirring rate of the high-speed mixer is 24000 rpm / min; (6) After the mold is coated with a release agent, the mixed material is transferred to the mold, and the mold containing the mixed material is transferred to a flat vulcanizer for compression molding. The molding temperature is 190° C., the molding pressure is 15 MPa, and the molding time is 10 min. The pressure is released and the mold is demolded to obtain a composite bipolar plate for a liquid flow battery with a thickness of 0.5 mm. The mass fraction of the polymer-based nanocomposite material is 65%, the mass fraction of the conductive filler is 31%, and the mass fraction of the fiber reinforcement material is 4%. Example 4
[0023] (1) 18 mL of 68% concentrated nitric acid and 12 mL of 98% concentrated sulfuric acid were sequentially added dropwise to 500 mg of carbon nanotubes, the suspension was uniformly dispersed by ultrasonication for 2 h, the mixture was centrifuged, and then washed with deionized water until the pH value of the solution reached neutral, and then dried to obtain carboxylated carbon nanotubes; (2) 0.28 g of carboxylated carbon nanotubes was added to a mixed solution of 60 mL of DMF and 40 mL of THF, and ultrasonicated until completely dispersed. Then, 8.12 g of PVDF-hfp was added, stirred for 10 h, and dried for 10 h to obtain the PVDF-hfp-based nanocomposite material.
[0024] (3) Weigh 8.4 g PVDF-HFP-based nanocomposite, 1.4 g Ketjen black, 3.78 g flake graphite, and 0.42 g carbon fiber; (4) Pour the weighed material into a mortar grinder and grind for 10 minutes; (5) Pour the ground material into a high-speed mixer and mix for 20 seconds, where the stirring rate of the high-speed mixer is 24000 rpm / min; (6) After the mold is coated with a release agent, the mixed material is transferred to the mold, and the mold containing the mixed material is transferred to a flat vulcanizer for compression molding. The molding temperature is 190° C., the molding pressure is 15 MPa, and the molding time is 5 min. The pressure is released and the mold is demolded to obtain a composite bipolar plate for a liquid flow battery with a thickness of 0.65 mm. The mass fraction of the polymer-based nanocomposite material is 60%, the mass fraction of the conductive filler is 37%, and the mass fraction of the fiber reinforcement material is 3%. Example 5
[0025] (1) 15 mL of 68% concentrated nitric acid and 15 mL of 98% concentrated sulfuric acid were sequentially added dropwise to 500 mg of carbon nanotubes. The suspension was uniformly dispersed by ultrasonication for 2 h. The mixture was centrifuged and then washed with deionized water until the pH value of the solution reached neutral. After drying, carboxylated carbon nanotubes were obtained. (2) 0.28 g of carboxylated carbon nanotubes was added to a mixed solution of 60 mL of DMF and 40 mL of THF, and ultrasonicated until completely dispersed. Then, 8.12 g of PVDF was added, stirred for 12 h, and dried for 10 h to obtain the PVDF-based nanocomposite material.
[0026] (3) Weigh 8.4 g of PVDF-based nanocomposite, 1.4 g of Ketjen black, 2.8 g of flake graphite, 0.7 g of expanded graphite, and 0.7 g of carbon nanofiber; (4) Pour the weighed material into a mortar grinder and grind for 10 minutes; (5) Pour the ground material into a high-speed mixer and mix for 30 seconds, where the stirring rate of the high-speed mixer is 24000 rpm / min; (6) After the mold is coated with a release agent, the mixed material is transferred to the mold, and the mold containing the mixed material is transferred to a flat vulcanizer for compression molding. The compression molding temperature is 190° C., the compression molding pressure is 15 MPa, and the compression molding time is 10 min. The pressure is released and the mold is demolded to obtain a composite bipolar plate for a liquid flow battery with a thickness of 0.55 mm. The mass fraction of the polymer-based nanocomposite material is 60%, the mass fraction of the conductive filler is 35%, and the mass fraction of the fiber reinforcement material is 5%. Example 6
[0027] (1) 18 mL of 68% concentrated nitric acid and 12 mL of 96% concentrated sulfuric acid were sequentially added dropwise to 500 mg of carbon nanotubes, the suspension was uniformly dispersed by ultrasound for 2 h, the mixture was centrifuged, and then washed with deionized water until the pH value of the solution reached 7, and then dried for 7 h to obtain carboxylated carbon nanotubes; (2) 0.28 g of carboxylated carbon nanotubes was added to a mixed solution of 50 mL of DMF and 50 mL of THF, and ultrasonicated until completely dispersed. Then, 8.82 g of PVDF-hfp was added, stirred for 10 h, and dried for 12 h to obtain the PVDF-hfp-based nanocomposite material.
[0028] (3) Weigh 8.4 g PVDF-HFP-based nanocomposite, 3.22 g Ketjen black, 0.98 g expanded graphite, and 1.4 g carbon nanofiber; (4) Pour the weighed material into a mortar grinder and grind for 8 minutes; (5) Pour the ground material into a high-speed mixer and stir for 30 seconds, where the stirring rate of the high-speed mixer is 23000 rpm / min; (6) After the mold is coated with a release agent, the mixed material is transferred to the mold, and the mold containing the mixed material is transferred to a flat vulcanizer for compression molding. The compression molding temperature is 200° C., the compression molding pressure is 5 MPa, and the compression molding time is 10 min. The pressure is released and the mold is demolded to obtain a composite bipolar plate for a liquid flow battery with a thickness of 0.7 mm. The mass fraction of the polymer-based nanocomposite material is 60%, the mass fraction of the conductive filler is 30%, and the mass fraction of the fiber reinforcement material is 10%. Comparative Example 1
[0029] (1) 15 mL of 68% concentrated nitric acid and 15 mL of 98% concentrated sulfuric acid were sequentially added dropwise to 500 mg of carbon nanotubes, the suspension was uniformly dispersed by ultrasound for 2 h, the mixture was centrifuged, and then washed with deionized water until the pH value of the solution reached 7, and then dried for 8 h to obtain carboxylated carbon nanotubes; (2) Weigh 8.12 g PVDF, 0.28 g carboxylated carbon nanotubes, 1.4 g Ketjen black, 2.8 g flake graphite, 0.7 g expanded graphite, and 0.7 g carbon nanofibers; (3) Pour the weighed material into a mortar grinder and grind for 10 minutes; (4) Pour the ground material into a high-speed mixer and mix for 30 seconds, where the stirring rate of the high-speed mixer is 24000 rpm / min; (5) After the mold is coated with a release agent, the mixed material is transferred to the mold, and the mold containing the mixed material is transferred to a flat vulcanizer for compression molding. The compression molding temperature is 190° C., the compression molding pressure is 10 MPa, and the compression molding time is 15 min. The pressure is released and the mold is demolded to obtain a composite bipolar plate for a liquid flow battery with a thickness of 0.6 mm. The mass fraction of the polymer is 58%, the mass fraction of the carboxylated carbon nanotubes is 2%, the mass fraction of the conductive filler is 35%, and the mass fraction of the fiber reinforcement material is 5%. Comparative Example 2
[0030] (1) 15 mL of 68% concentrated nitric acid and 15 mL of 98% concentrated sulfuric acid were sequentially added dropwise to 500 mg of carbon nanotubes, the suspension was uniformly dispersed by ultrasound for 2 h, the mixture was centrifuged, and then washed with deionized water until the pH value of the solution reached 7, and then dried for 6 h to obtain carboxylated carbon nanotubes; (2) 0.28 g of carboxylated carbon nanotubes was added to a mixed solution of 60 mL of DMF and 40 mL of THF, and ultrasonicated until completely dispersed. Then, 8.12 g of PVDF was added, stirred for 12 h, and dried for 10 h to obtain the PVDF-based nanocomposite material.
[0031] (3) Weigh 8.4 g of PVDF-based nanocomposite, 1.4 g of Ketjen black, 2.8 g of flake graphite, 0.7 g of expanded graphite, and 0.7 g of carbon nanofiber; (4) Pour the weighed material into a mortar grinder and grind for 10 minutes; (5) After the mold is coated with a release agent, the mixed material is transferred to the mold, and the mold containing the mixed material is transferred to a flat vulcanizer for compression molding. The compression molding temperature is 190° C., the compression molding pressure is 15 MPa, and the compression molding time is 10 min. The pressure is released and the mold is demolded to obtain a composite bipolar plate for a liquid flow battery with a thickness of 0.65 mm. The mass fraction of the polymer-based nanocomposite material is 60%, the mass fraction of the conductive filler is 35%, and the mass fraction of the fiber reinforcement material is 15%. Comparative Example 3
[0032] (1) 15 mL of 68% concentrated nitric acid and 15 mL of 98% concentrated sulfuric acid were sequentially added dropwise to 500 mg of carbon nanotubes, the suspension was uniformly dispersed by ultrasound for 2 h, the mixture was centrifuged, and then washed with deionized water until the pH value of the solution reached 7, and then dried for 6 h to obtain carboxylated carbon nanotubes; (2) 0.28 g of carboxylated carbon nanotubes was added to a mixed solution of 60 mL of DMF and 40 mL of THF, and ultrasonicated until completely dispersed. Then, 8.12 g of PVDF was added, stirred for 12 h, and dried for 10 h to obtain the PVDF-based nanocomposite material.
[0033] (3) Weigh 8.4 g of PVDF-based nanocomposite, 1.4 g of Ketjen black, 2.8 g of flake graphite, 0.7 g of expanded graphite, and 0.7 g of carbon nanofiber; (4) Pour the weighed material into a mortar grinder and grind for 10 minutes; (5) Pour the ground material into a high-speed mixer and mix for 30 seconds, where the stirring rate of the high-speed mixer is 15000 rpm / min; (6) After the mold is coated with a release agent, the mixed material is transferred to the mold, and the mold containing the mixed material is transferred to a flat vulcanizer for compression molding. The compression molding temperature is 190° C., the compression molding pressure is 15 MPa, and the compression molding time is 10 min. The pressure is released and the mold is demolded to obtain a composite bipolar plate for a liquid flow battery with a thickness of 0.65 mm. The mass fraction of the polymer-based nanocomposite material is 60%, the mass fraction of the conductive filler is 35%, and the mass fraction of the fiber reinforcement material is 15%. Comparative Example 4
[0034] (1) 15 mL of 68% concentrated nitric acid and 15 mL of 98% concentrated sulfuric acid were sequentially added dropwise to 500 mg of carbon nanotubes, the suspension was uniformly dispersed by ultrasound for 2 h, the mixture was centrifuged, and then washed with deionized water until the pH value of the solution reached 7, and then dried for 6 h to obtain carboxylated carbon nanotubes; (2) 0.28 g of carboxylated carbon nanotubes was added to a mixed solution of 60 mL of DMF and 40 mL of THF, and ultrasonicated until completely dispersed. Then, 8.12 g of PVDF was added, stirred for 12 h, and dried for 10 h to obtain the PVDF-based nanocomposite material.
[0035] (3) Weigh 8.4 g of PVDF-based nanocomposite, 1.4 g of Ketjen black, 2.8 g of flake graphite, 0.7 g of expanded graphite, and 0.7 g of carbon nanofiber; (4) Pour the weighed material into a mortar grinder and grind for 10 minutes; (5) Pour the ground material into a high-speed mixer and mix for 30 seconds, where the stirring rate of the high-speed mixer is 30000 rpm / min; (6) After the mold is coated with a release agent, the mixed material is transferred to the mold, and the mold containing the mixed material is transferred to a flat vulcanizer for compression molding. The compression molding temperature is 190° C., the compression molding pressure is 15 MPa, and the compression molding time is 10 min. The pressure is released and the mold is demolded to obtain a composite bipolar plate for a liquid flow battery with a thickness of 0.65 mm. The mass fraction of the polymer-based nanocomposite material is 60%, the mass fraction of the conductive filler is 35%, and the mass fraction of the fiber reinforcement material is 15%.
[0036] The tensile properties, bending properties and electrical conductivity of the bipolar plate materials of Examples 1-6 and Comparative Examples 1-4 were tested, and the results are shown in Table 1.
[0037]
[0038] The bipolar plate prepared by the method of the present invention has a smooth surface, a stable and tough structure, and effectively improves the mechanical properties and conductive properties of the composite bipolar plate for liquid flow batteries by controlling the content of polymer-based nanocomposites, conductive fillers, and fiber-reinforced materials. By doping carboxyl carbon nanotubes in fluorine-containing polymers, polymer-based nanocomposites are prepared, and then blended with conductive fillers and fiber-reinforced materials to obtain high-performance composite bipolar plates with uniform material distribution. The method has a simple preparation process, does not require multiple heating, can save energy, and is easy to continuously industrialize. In addition, the strong interaction between the carboxyl groups in the surface carboxyl-modified nanofillers and the CF2 in PVDF and PVDF-hfp is conducive to better fusion of the two powders. The high-speed stirring treatment further narrows the gap between the particle sizes of the polymer and the conductive carbon material, strengthens the interaction between the polymer and the conductive carbon material, further improves the distribution uniformity of each component in the powder, has a certain effect on improving the uniformity, conductivity and mechanical strength of the formed plate, and makes the plate have a lower contact resistance with the electrode.
[0039] Figure 1The sample pictures of the composite bipolar plates prepared in Example 5 and Comparative Example 1 clearly show that the surface of the bipolar plate with the addition of the polymer-based nanocomposite material exhibits good uniformity, while the surface of the composite bipolar plate prepared only by simple physical mixing is rough.
[0040] The prepared bipolar plates were tested for mechanical properties and electrical conductivity (Table 1). The mechanical properties of the samples in each embodiment were similar. Comparing Examples 1-6 and Comparative Example 1, polymer-based nanocomposites were used in the embodiments, carboxylated carbon nanotubes were closely attached to the surface of the polymer, and then fully mixed with other carbon materials through high-speed stirring, which greatly enhanced the contact space and interaction between the polymer-based composite material and the carbon material, and played an important role in improving the uniformity of the composite bipolar plate, which was specifically manifested in the substantial improvement of mechanical properties and electrical conductivity, which was significantly better than Comparative Example 1 which did not use polymer-based nanocomposites. Analysis of the data of Examples 1-6 and Comparative Examples 2-4 shows that the embodiments use high-speed stirring, and the stirring rate is selected between 20000-24000rpm / min, which reduces the size difference between the components of the powder. Comparative Examples 2-4 show that too low a stirring rate will make the materials not evenly mixed together, and too high a stirring rate will reduce the fineness of the materials and fail to build a good conductive network. The samples stirred at 20000-24000rpm / min (Examples 1-6) showed better conductivity. Nano-scale Ketjen black has a unique branched morphology and high specific surface area. High-speed stirring allows Ketjen black to be better filled between the materials, forming an efficient and tight conductive network, thereby improving the conductivity of the composite bipolar plate. In addition, the thickness of the prepared composite bipolar plates is between 0.5 and 0.7 mm. By testing the mechanical properties and conductivity of the prepared bipolar plates, it can be found that within the same thickness range, the bipolar plates prepared by pre-preparing nanocomposites and using high-speed stirring (Examples 1-6) show better mechanical properties and conductivity, which further proves that a more uniformly mixed composite bipolar plate can be obtained by this method.
[0041] The above-described specific embodiments further illustrate the present invention in detail, but these descriptions cannot be understood as limiting the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite bipolar plate for a flow battery, characterized in that: The steps include: (1) treating the carbon nanotubes with an oxidation treatment using a mixed acid of concentrated nitric acid and concentrated sulfuric acid to obtain carboxylated carbon nanotubes; (2) adding the carboxylated carbon nanotubes obtained in step (1) to a mixed solution of N,N-dimethylformamide and tetrahydrofuran, ultrasonicating until completely dispersed, then adding a fluorine-containing polymer, stirring, and drying to obtain a polymer-based nanocomposite material; (3) The polymer-based nanocomposite material, the conductive filler and the fiber-reinforced material obtained in step (2) are mixed, ground for 5 to 10 minutes, and then stirred at high speed and compression molded to obtain a composite bipolar plate for a liquid flow battery.
2. The method for preparing a composite bipolar plate for a flow battery according to claim 1, characterized in that: In the step (1), the mass fraction of concentrated nitric acid is 65%-68%, the mass fraction of concentrated sulfuric acid is 95%-98%, the volume ratio of concentrated nitric acid to concentrated sulfuric acid is 1-1.5:1, and the mass volume ratio of carbon nanotubes to concentrated nitric acid-concentrated sulfuric acid mixed acid is 400-500 mg:30 mL.
3. The method for preparing a composite bipolar plate for a flow battery according to claim 1, characterized in that: In the step (2), the volume ratio of N,N-dimethylformamide to tetrahydrofuran is 1-1.5:1; the mass volume ratio of carboxylated carbon nanotubes to N,N-dimethylformamide solution is 0.28 g:50-72 mL; the fluorine-containing polymer is polyvinylidene fluoride or polyvinylidene fluoride-hexafluoropropylene copolymer; the mass ratio of the fluorine-containing polymer to the carboxylated carbon nanotubes is 29-31.5:1, the stirring time is 8-12 hours, and the drying time is 10-12 hours.
4. The method for preparing a composite bipolar plate for a flow battery according to claim 1, characterized in that: In the step (3), the conductive filler comprises one or both of flake graphite and expanded graphite and Ketjen black; the fiber reinforcement material is carbon nanofiber or carbon fiber; the mass ratio of the polymer-based nanocomposite material, the conductive filler, and the fiber reinforcement material is 6-6.5:3-3.7:0.3-1; and the high-speed stirring speed is 22000-24000 rpm / min for 15-30 s.
5. The method for preparing a composite bipolar plate for a flow battery according to claim 1, characterized in that: In the step (3), the molding temperature is 190-200°C, the pressure is 5-15 MPa, and the time is 5-15 min.
6. A composite bipolar plate for a liquid flow battery, characterized in that: The method is prepared according to any one of claims 1 to 5.
7. An application of the composite bipolar plate for a flow battery as claimed in claim 6, characterized in that: The composite bipolar plate for a liquid flow battery is applied to a liquid flow battery.
Citation Information
Patent Citations
Bipolar plate for all-vanadium redox flow battery and preparation method of bipolar plate
CN117207561A
Composite binder containing carbon nanotube and lithium secondary battery employing the same
CN101243566A
Binder for electrode of lithium battery and lithium battery containing the binder
CN103199257A
Composite bipolar board for fuel cell and preparation method thereof
CN109546161A
Preparation method of positive electrode composite conductive binding agent for lithium ion battery
CN109755579A